ICES report on ocean climate 2020 - Albretsen, Jon; von Appen, Wilken-Jon; Berx, Barbara; Beszczynska-Möller, Agnieszka; Chafik, Léon; Cisewski, Boris; Cusack, Caroline; Cyr, Frédéric; Daly, Eoghan; Danielsen, Magnus; Desbruyères, Damien; Dummermuth, Angelika; et al. (ICES, 2022)
We are very pleased to present the International Council for the Exploration of the Sea (ICES) report on ocean climate (IROC) 2020. The IROC production is a credit to the tireless efforts and long-term commitment of the international experts who are members of the ICES Working Group on Ocean Hydrography (WGOH). This report provides a combined analysis of the ocean-hydrography observations that are regularly collected at multiple stations in the ICES regions of the North Atlantic and its adjacent seas. The best possible overview of ocean changes is presented based on measurements of temperature and salinity over time, with several time-series dating back from multiple decades to over a century. The Covid-19 pandemic affected the IROC 2020 service delivery, due to continued disruptions and travel restrictions in many countries that hampered ocean observing activities. Expert group members encountered varying challenges, including personal experiences (e.g. school closures), impacts on data-collection efforts, and issues accessing oceanographic sites. During the COVID-19 pandemic, WGOH meetings were held online, with virtual gatherings in spring and autumn 2021. These online meetings provided the opportunity for more members to engage in discussions. WGOH welcomed five new members from Germany, Ireland, and UK in 2021. While the WGOH membership (61) has increased, we would like extend our heartfelt gratitude to colleagues who stepped down recently. In particular, special thanks to Penny Holliday [National Oceanographic Centre (NOC), UK] and Holger Klein (Federal Maritime and Hydrographic Agency, Germany) for their many years of service organizing oceanographic campaigns and providing highly valued contributions to the IROC and wider WGOH activities. We envisage that 2022 will be a dynamic year for WGOH members, with the upcoming UN Decade of Ocean Science for Sustainable Development endorsed conference “ICES/NAFO 4th Decadal Variability of the North Atlantic and its Marine Ecosystems: 2010–2019 Symposium” scheduled ...